2018
DOI: 10.1007/s00426-018-1015-6
|View full text |Cite
|
Sign up to set email alerts
|

Putting emotions in routes: the influence of emotionally laden landmarks on spatial memory

Abstract: The aim of this study was to assess how people memorize spatial information of emotionally laden landmarks along a route and if the emotional value of the landmarks affects the way metric and configurational properties of the route itself are represented. Three groups of participants were asked to watch a movie of a virtual walk along a route. The route could contain positive, negative, or neutral landmarks. Afterwards, participants were asked to: (a) recognize the landmarks; (b) imagine to walk distances betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
3
34
0
1
Order By: Relevance
“…Indeed, in tracking the route on the map participants with high/low positive emotional landmarks and low negative emotional landmarks were more accurate than neutral landmarks and high negative emotional landmarks. These findings are in line with Ruotolo et al's results [11], revealing that participants in the positive condition were more accurate than those in the neutral condition in drawing the route as well as in indicating the landmarks location. In addition, Palmiero and Piccardi [3] highlighted that emotional landmarks, especially positive, promote accurate spatial representation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, in tracking the route on the map participants with high/low positive emotional landmarks and low negative emotional landmarks were more accurate than neutral landmarks and high negative emotional landmarks. These findings are in line with Ruotolo et al's results [11], revealing that participants in the positive condition were more accurate than those in the neutral condition in drawing the route as well as in indicating the landmarks location. In addition, Palmiero and Piccardi [3] highlighted that emotional landmarks, especially positive, promote accurate spatial representation.…”
Section: Discussionsupporting
confidence: 92%
“…In this vein, the key role of emotional landmarks defined in terms of valence (positive/pleasant vs. negative/unpleasant) and arousal (activating/excited vs. deactivating/calm) has only recently been investigated [3,10,11], demonstrating that positive/negative emotions increasing landmark's salience improve performance in navigational memory tasks. More specifically, Palmiero and Piccardi [3] observed that both positive and negative emotional landmarks equally enhanced the ability to learn a path, but just positive emotional ones improved the reproduction of the path on the map.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this evaluation of the event is the object of a separate question and is not necessarily related to the emotion actually triggered during the event, this difference between participants is consistent with the absence of joy observed in the experimental group. This finding is interesting from a wayfinding perspective, as it converges with existing evidence in the literature that emotion structures spatial representations (Storbeck and Maswood, 2016;Ruotolo et al, 2019). In particular, it has been reported that being in a positive mood and feeling positive emotions enhance spatial working memory by favoring a better retention of spatial information, in comparison to being in a negative mood (Storbeck and Maswood, 2016).…”
Section: Subjective Experience Of the Complex Situations: Negative Emsupporting
confidence: 86%
“…In particular, it has been reported that being in a positive mood and feeling positive emotions enhance spatial working memory by favoring a better retention of spatial information, in comparison to being in a negative mood (Storbeck and Maswood, 2016). Emotion has also been shown to affect spatial representations: participants who see landmarks inducing positive emotions while walking along a virtual route are able to locate the landmarks more accurately on a map afterward, as well as drawing the route, in comparison to participants who see landmarks inducing negative emotions (Ruotolo et al, 2019). These findings have led some researchers to advocate the use of positive emotion to improve wayfinding apps in everyday life, for example by computing instructions and routes based on street segments previously evaluated positively by users to allow for an "emotional" wayfinding (Gartner, 2012;Huang et al, 2014).…”
Section: Subjective Experience Of the Complex Situations: Negative Emmentioning
confidence: 99%